2015
DOI: 10.1182/blood-2014-04-572750
|View full text |Cite
|
Sign up to set email alerts
|

ATL response to arsenic/interferon therapy is triggered by SUMO/PML/RNF4-dependent Tax degradation

Abstract: Key Points• Survival of ATL cells depends on continuous Tax expression.• Arsenic/interferon combination induces SUMO/PML/RNF4-mediated Tax degradation.The human T-cell lymphotropic virus type I (HTLV-1) Tax transactivator initiates transformation in adult T-cell leukemia/lymphoma (ATL), a highly aggressive chemotherapyresistant malignancy. The arsenic/interferon combination, which triggers degradation of the Tax oncoprotein, selectively induces apoptosis of ATL cell lines and has significant clinical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 44 publications
5
65
0
Order By: Relevance
“…These results are consistent with previous reports of the AZT effect, in vivo and in vitro, inhibiting telomerase activity and causing a stabilization and reactivation of p53, p21 and p27, thus inducing cell apoptosis [96]. The combination of IFN and arsenic has also proven to cause cell apoptosis mediated by Tax degradation, and has also been proposed as an alternative therapy [97,98].…”
Section: Pathogenesis and Clinical Featuressupporting
confidence: 93%
“…These results are consistent with previous reports of the AZT effect, in vivo and in vitro, inhibiting telomerase activity and causing a stabilization and reactivation of p53, p21 and p27, thus inducing cell apoptosis [96]. The combination of IFN and arsenic has also proven to cause cell apoptosis mediated by Tax degradation, and has also been proposed as an alternative therapy [97,98].…”
Section: Pathogenesis and Clinical Featuressupporting
confidence: 93%
“…Moreover, NB aggregation is regulated by arsenic or other oxidative stresses (Zhu et al 1997;Lallemand-Breitenbach et al 2001;Sahin et al 2014). Enforcing PML expression can facilitate SUMO-initiated proteolysis (Guo et al 2014;Sahin et al 2014;Dassouki et al 2015). Interferon-induced senescence seems to require PML and is enforced by p53 (Chiantore et al 2012;Fu et al 2015).…”
Section: The Unexpected Role Of Normal Pml In Therapy Responsementioning
confidence: 99%
“…Similarly, the combination of interferon and arsenic, which enforces maximal NB formation and partner recruitment (Quignon et al 1998), exerts clinical activity in HTLV-I associated adult T-cell leukemia (Kchour et al 2009;Bazarbachi et al 2011). This likely reflects the degradation of the HTLV-I tax transactivator, an initiator, and a likely driver of ATL by a PML/SUMO/RNF4-dependent mechanism (El-Sabban et al 2000;El Hajj et al 2010;Dassouki et al 2015). Clinical efficacy of this combination may also involve activation of a PML/p53 senescence checkpoint.…”
Section: The Unexpected Role Of Normal Pml In Therapy Responsementioning
confidence: 99%
“…Today, Dr. Bazarbachi and his colleagues continue their eff orts to improve on those survival rates through a variety of research eff orts. They demonstrated, for example, that ATL‐derived cells are addicted to continuous expression of the viral oncoprotein Tax, indicating that Tax degradation underlies clinical responses in mice and patients . Furthermore, they demonstrated that treatment with arsenic/interferon targets Tax, which could lead to greater survival among patients with ATL.…”
Section: Building On the Researchmentioning
confidence: 99%
“…Th ey demonstrated, for example, that ATL-derived cells are addicted to continuous expression of the viral oncoprotein Tax, indicating that Tax degradation underlies clinical responses in mice and patients. 2 Furthermore, they demonstrated that treatment with arsenic/interferon targets Tax, which could lead to greater survival among patients with ATL. Although this treatment is not yet part of international guidelines, it currently is being tested in ongoing clinical trials, he reports.…”
Section: Building On the Researchmentioning
confidence: 99%